Hesperetin attenuates cognitive dysfunction via SIRT6/NLRP3 pathway in scopolamine-induced mice - Jing, Shangwen; Wang, Xinyue; Zhang, Zerong; Cao, Dandan; Huang, Kongli; Wang, Yuting; Liu, Zhuangzhuang; Su, Shijie; Wang, Qi (Metabolic brain disease, 2023)
Neuroinflammation is a critical feature in the pathogenesis of neurodegenerative disorders such as Alzheimer’s disease (AD). Hesperetin can exert anti-inflammatory, antioxidant and other neuroprotective effects. In this study, the scopolamine (SCOP)-induced cognitive dysfunction in mice model was used to evaluate the neuroprotective effects of hesperetin. Behavioral tests (Morris water maze, open field, and novel object recognition tests) were conducted to evaluate the effect of hesperetin on cognitive dysfunction behaviors. Nissl staining and Immunofluorescence were used to evaluate hippocampal neuronal damage and microglial activation in mice. The levels of proinflammatory factors, oxidant stress, and the cholinergic neurotransmitter were detected by real-time quantitative fluorescence PCR (RT-qPCR) or biochemical reagent kits. Western blotting was used to detect the relative protein expression of the sirtuin 6 (SIRT6) / NOD-like receptor thermal protein domain associated protein 3 (NLRP3) pathway. Results showed that hesperetin could ameliorate SCOP-induced cognitive impairment and neuronal damage, and regulate the levels of cholinergic neurotransmitters in the hippocampal of AD mice. Hesperetin could also enhance antioxidant defense by regulating the levels of reactive oxygen species (ROS), malondialdehyde (MDA), superoxide dismutase (SOD), and catalase (CAT). Hesperetin exerted anti-neuroinflammation effects through inhibiting of microglia activation and down-regulating the mRNA transcript levels of inflammatory cytokines, such as tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS). Meanwhile, hesperetin could attenuate the expression of NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC), thioredoxin-interacting protein (TXNIP), and caspase-1 p20 and upregulate the expression of SIRT6 in SCOP-induced mice. Overall, our study suggested that hesperetin might ameliorate SCOP-induced cognitive dysfunction by improving cholinergic system dysfunction and suppressing oxidative stress and attenuating neuroinflammation via SIRT6/NLRP3 pathway in mice.